A Comparative Study Of The Kayon In The Shadow Puppet Theatre Of Java, Bali And Kelantan: A Visual And Interpretive Understanding Of Its Symbols - Kingham, Sugu P. J. (2011)

(untitled)
The kayon of Java, known also as kakayonan in Bali, and referred to as the pohon beringin in Kelantan, is an ornate tree-or leaf-shaped puppet with which all shadow puppet theatre performances across these locations are formally opened and closed. A tree-shaped figure, with equivalent functions, does not appear in the shadow puppet theatre outside Indonesia and Malaysia. However, it appears in a disguised fashion in the Thai nang talung version of the shadow puppet theatre (the sage carries in his hand an object that resembles the kayon).